2019
DOI: 10.3389/fnins.2019.00570
|View full text |Cite
|
Sign up to set email alerts
|

Musical Attention Control Training for Psychotic Psychiatric Patients: An Experimental Pilot Study in a Forensic Psychiatric Hospital

Abstract: Poor attention skills constitute a major problem for psychiatric patients with psychotic symptoms, and increase their chances of treatment drop-out. This study investigated possible benefits of musical attention control training (MACT). To examine the effect of MACT on attention skills of psychiatric patients with psychotic features a randomized controlled trial (RCT) was conducted in a forensic psychiatric clinic. Participants ( N = 35, age M = 34.7, 69% male) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…The researchers used the fact that music allows for the correction of step frequency and improvement of gait pattern, mainly through the action of auditory motor feedback to reduce stress, both motor and psychological. File S4 [ 4 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Resultsmentioning
confidence: 99%
“…The researchers used the fact that music allows for the correction of step frequency and improvement of gait pattern, mainly through the action of auditory motor feedback to reduce stress, both motor and psychological. File S4 [ 4 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Resultsmentioning
confidence: 99%
“…Although there is a lack of research examining the efficacy of music therapy for this specific population (Hakvoort et al , 2015), music therapy is being implemented in prison and forensic settings (Sicard, 2021). Moreover, the existing research in recent years has offered promising results with offender populations, including those with complex needs (Kellett et al , 2018; Macfarlane et al , 2019; van Alphen et al , 2019; Frederiksen et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The study also reported that the program was simple to implement, there was a significantly low drop-out rate and offenders were satisfied with the program (Kellett et al , 2018). Moreover, there are several studies that have demonstrated promising results for music therapy programs for forensic patients with schizophrenia (Compton Dickinson and Hakvoort, 2017; van Alphen et al , 2019; Frederiksen et al , 2020) and for those with other serious mental illnesses such as borderline personality disorder (Walker and Paton, 2014). Therefore, while there is limited research for music therapy for HROs with complex needs, the existing research has demonstrated several key benefits for offending cohorts with complex needs.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report of a music therapy intervention targeting attention and diminishing arousal in an adult male penitentiary psychiatric population diagnosed with PTSD. In a pilot study in a forensic psychiatric hospital Van Alphen, Stams, and Hakvoort (2019) found that MACT had a positive effect on attention skills, but that study was not directed at targeting PTSD Cutoff score is for DSM-IV-R diagnosis of PTSD = 15, maximum score is 51 *Effect size measured as a decline (-) or increase (+) in percentage of PTSD-symptoms compared to entrance screening.…”
Section: Discussionmentioning
confidence: 99%